Identification of Proteomic Markers in Head and Neck Cancer Using MALDI–MS Imaging, LC–MS/MS, and Immunohistochemistry. Issue 1 (26th November 2018) - Hoffmann, Franziska; Umbreit, Claudia; Krüger, Thomas; Pelzel, Daniela; Ernst, Günther; Kniemeyer, Olaf; Guntinas‐Lichius, Orlando; Berndt, Alexander; von Eggeling, Ferdinand
Abstract : Purpose: The heterogeneity of squamous cell carcinoma tissue greatly complicates diagnosis and individualized therapy. Therefore, characterizing the heterogeneity of tissue spatially and identifying appropriate biomarkers is crucial. MALDI–MS imaging (MSI) is capable of analyzing spatially resolved tissue biopsies on a molecular level. Experimental design: MALDI–MSI is used on snap frozen and formalin‐fixed and paraffin‐embedded (FFPE) tissue samples from patients with head and neck cancer (HNC) to analyze m/z values localized in tumor and nontumor regions. Peptide identification is performed using LC–MS/MS and immunohistochemistry (IHC). Results: In both FFPE and frozen tissue specimens, eight characteristic masses of the tumor's epithelial region are found. Using LC–MS/MS, the peaks are identified as vimentin, keratin type II, nucleolin, heat shock protein 90, prelamin‐A/C, junction plakoglobin, and PGAM1. Lastly, vimentin, nucleolin, and PGAM1 are verified with IHC. Conclusions and Clinical Relevance: The combination of MALDI–MSI, LC‐MS/MS, and subsequent IHC furnishes a tool suitable for characterizing the molecular heterogeneity of tissue. It is also suited for use in identifying new representative biomarkers to enable a more individualized therapy.